Detection of avian polyomavirus from psittacine birds in Klang Valley - Zanon, Zamir (2016)
Avian polyomavirus (APV) primarily affects young birds and can cause mortality in wide range of psittacine and non-psittacine birds.Adult birds typically are resistant to infection; they will seroconvert and shed the virus for up to 90 days, then clear the infection. The typical presentation of APV-infected birds is a well-fleshed juvenile, just before fledgling age, with acute onset of lethargy, crop stasis, and death within 24–48 hour. Other clinical signs are cutaneous hemorrhage, abdominal distention, and feather abnormalities. Surviving budgerigars with age more than three week-old often exhibit feather dystrophy (French molt or feather dusters). This is the first study to detect the presence of APV in Malaysia. Therefore, a preliminary study was conducted to detect the presence of avian polyomavirus among psittacine birds especially in parrot species in Klang Valley by using polymerase chain reaction (PCR) technique. A total of 85 faecal samples were collected from psittacines‟ species of individual pet owners and parrot breeders. DNA was isolated from feces of 85 symptom-free psittacine birds taken from four different breeders from Klang Valley. The presence of APV was analyzed by performing polymerase chain reaction assays (PCR) and agarose gel electrophoresis (AGE) using specific primers targeting VP1 (5‟-CTTATGTGGGAGGCTGCAGTGTT-3‟ and 5‟-TACTGAAATAGCGTGGTAGGCCTC-3‟) and APV full length (5‟- ACAATGCCTAACGGAACGCC-3‟, 5‟-CACCGAAGCGGCGATACTATA-3‟, 5‟-GAGGCCTACCACGCTATTTCAGTA-3‟ and 5‟-GCACTTAGCGCCTGTCCAAT-3‟) genes. Positive results were detected in six out of 30 pooled samples (20%) which were from yellow-collared macaw, blue-headed parrot, red-crowned macaw, sulphur-crested cockatoo, blue-throated macaw and Pesquet‟s parrot.As a conclusion, presence of APV in psittacine birds has been successfully detected.